ESTIMATE OF DAILY REFERENCE EVAPOTRANSPIRATION AT FORMIGA, MG, BRAZIL - da Paz, L. R.; Thebaldi, M. S. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The evapotranspiration quantification has a great importance on water resources management, hydrological and meteorological modeling and on sustainable water management of irrigated crops. Therefore, this paper aims to estimate the daily reference evapotranspiration (ET0), in Formiga, MG, Brazil, using the Penman-Monteith´s Method under FAO standards and other three empirical methods. The daily reference evapotranspiration (ET0) estimation was carried out from data provided by INMET, collected by an automatic weather station, between the years 2007 and 2014. In addition, the empirical constants of Hargreaves, Makkink and Camargo Methods were fit, to represent better the local conditions. For method´s performance analysis, were considered: the reliability index (c), concordance index (d), correlation (r) and determination coefficients (R2); mean absolute error (MAE) and square root of the mean square error (SRME). It was found that the method of Makkink, after adjustment, produced the best estimates for daily reference evapotranspiration of the Formiga, MG.